A PROPOSED SYLLABUS OF CRITICAL READING FOR THE ENGLISH DEPARTMENT STUDENTS OF BRAWIJAYA UNIVERSITY - Emy Sudarwati (Universitas Brawijaya, 2013)
The purpose of this study is developing an appropriate Critical Reading syllabus for English department students of Brawijaya university. This study uses Research and Development design with a procedure which consists of needs analysis, description of the purpose, selection or development of syllabus type, production of proto syllabus, production of pedagogical syllabus expert validation, evaluation and revision, try out, final product. The final version of the product consists of Critical Reading syllabus. The product has been developed by following the stages in the modified Yalden’s model Keywords: critical reading, syllabus